Mechanisms of redox balance and inflammatory response after the use of methylprednisolone in children with multisystem inflammatory syndrome associated with COVID-19 - Krasic, Stasa; Vukomanovic, Vladislav; Ninic, Sanja; Pasic, Srdjan; Samardzija, Gordana; Mitrovic, Nemanja; Cehic, Maja; Nesic, Dejan; Bajcetic, Milica (Frontiers in Immunology, 2023)
Background Multisystem inflammatory syndrome in children (MIS-C) associated with being infected with coronavirus-19 (COVID-19) is a life-threatening condition resulting from cytokine storm, increased synthesis of reactive oxygen species (ROSs), and hyperinflammation occurring in genetically predisposed children following an infection with SARS-CoV-2. Aim The primary aims of our study were to identify changes in the activity of antioxidant enzymes in erythrocytes and total oxidative status in plasma after being treated with methylprednisolone (MP). Methods A prospective cohort study of 67 children (56.7% male) under 18 with MIS-C being treated with MP was conducted at the Mother and Child Health Institute from January 2021 to April 2022. The impact of the therapy was assessed on the basis of the clinical condition, haematological and biochemical blood parameters, and echocardiographic findings. Results 59.7% of patients presented cardiovascular (CV) manifestations, while myocardial dysfunction was observed in half of all patients (50.7%). A severe clinical course was observed in 22/67 patients. Children with CV involvement had a significantly higher relative concentration of B lymphocytes and lower relative concentration of NK cells than patients without CV issues (p < 0.001 and p = 0.004, respectively). Patients with severe MIS-C had a lower relative count of NK cells than those with moderate MIS-C (p = 0.015). Patients with myocardial dysfunction had a higher total oxidative plasma status (TOPS) than children without (p = 0.05), which implicates pronounced oxidative stress in the former cohort. In patients with shock, lower erythrocytes superoxide dismutase (SOD) activity was observed on admission compared to patients without shock (p = 0.04). After MP was administered, TOPS was significantly reduced, while catalase (CAT) and SOD activity increased significantly. Treatment failure (TF) was observed in 6 patients, only females (p=0.005). These patients were younger (p=0.05) and had lower CAT activity on admission (p=0.04) than patients with favorable treatment responses. In the group of patients with TF, TOPS increased after treatment (before 176.2 ± 10.3 mV, after 199.0 ± 36.7 mV). Conclusion MP leads to rapid modulation of TOPS and increases the activity of antioxidant enzymes in erythrocytes resulting in clinical and echocardiographic improvement. Based on the observed changes in the activity of the antioxidant enzymes, we can conclude that s hydrogen peroxide is the dominant ROS in patients with MIS-C. Patients with TF showed reduced CAT activity, whereas the treatment with MP led to pronounced oxidation. This implies that low CAT activity may be a contraindication for using MP.